2005
DOI: 10.1002/hipo.20141
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity with the hippocampus during successful memory formation

Abstract: Although it is well established that the hippocampus is critical for episodic memory, little is known about how the hippocampus interacts with cortical regions during successful memory formation. Here, we used event-related functional magnetic resonance imaging (fMRI) to identify areas that exhibited differential functional connectivity with the hippocampus during processing of novel objects that were subsequently remembered or forgotten on a postscan test. Functional connectivity with the hippocampus was enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
135
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(155 citation statements)
references
References 77 publications
19
135
0
1
Order By: Relevance
“…Our finding may thus reflect increased allocation of neural resources to integrative mnemonic processes. In agreement, a previous study showed enhanced hippocampal-neocortical connectivity during successful memory encoding (15). An interesting parameter, however, is the directionality of such interactions (38): If such interactions indeed promote integration into cortical-cortical networks, one would expect directional dominance toward the neocortex.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our finding may thus reflect increased allocation of neural resources to integrative mnemonic processes. In agreement, a previous study showed enhanced hippocampal-neocortical connectivity during successful memory encoding (15). An interesting parameter, however, is the directionality of such interactions (38): If such interactions indeed promote integration into cortical-cortical networks, one would expect directional dominance toward the neocortex.…”
Section: Discussionsupporting
confidence: 86%
“…During encoding, neurons in medial prefrontal cortex (PFC) have been shown to exhibit unit activity that is phase locked to hippocampal theta oscillations (14). Moreover, functional connectivity between these regions as measured using functional MRI (fMRI) in humans has been shown to predict subsequent memory (15). Furthermore, there is evidence of postencoding reactivation of memory traces within similar circuits.…”
mentioning
confidence: 99%
“…This finding is also consistent with the results of a previous functional neuroimaging study, in which the MTL activity during successful encoding was functionally connected with the OFC and other cortical activity (Ranganath et al, 2005). Moreover, the OFC-MTL connection has been identified in human subjects using DTI (Powell et al, 2004).…”
Section: Functional Connectivity Between the Orbitofrontal And Medialsupporting
confidence: 91%
“…White matter connections between OFC and MTL have also been demonstrated using diffusion tensor imaging (DTI) in humans (Powell et al, 2004). Moreover, functional neuroimaging studies have shown that OFC and MTL are functionally connected during successful encoding (Ranganath, Heller, Cohen, Brozinsky, & Rissman, 2005), and are coactivated during the retrieval of positive autobiographical memories (Piefke, Weiss, Zilles, Markowitsch, & Fink, 2003). Yet, there is no direct evidence indicating that enhanced memory for happy faces reflects enhanced OFC and MTL activity and interactions between the two.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the role of de novo protein synthesis and gene expression around training in both structures is critical for memory formation and consolidation (Bekinschtein et al 2007;Alberini 2009), which is in line with correlative studies in humans showing that successful memory formation is associated with an increase in functional connectivity between the hippocampus and some cortical regions, including RSC (Ranganath et al 2005). The timing of some molecular requirements, however, is different for each structure.…”
Section: [Supplemental Materials Is Available For This Article]supporting
confidence: 63%